2023
DOI: 10.1093/europace/euad005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after cryoballoon ablation of paroxysmal atrial fibrillation with the PolarX or the Arctic Front Advance Pro: a prospective multicentre experience

Abstract: Aims The aim of this study was to compare procedural efficacy and safety, including 1-year freedom from AF recurrence, between the novel cryoballoon system PolarX (Boston Scientific) and the Arctic Front Advance Pro (AFA-Pro) (Medtronic), in patients with paroxysmal AF undergoing PVI. Methods and results This multicentre prospective observational study included 267 consecutive patients undergoing a first cryoablation procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 22 publications
(22 reference statements)
6
31
0
Order By: Relevance
“…Pilot studies have shown that POLARx cryoballoon has comparable efficacy, safety, and short-term ablation outcomes compared to Medtronic's cryoballoon. 12,[20][21][22] In a study of 317 patients, Heeger et al 11 did not find any pop-out phenomenon during AF ablation with POLARx. Similarly, Tilz et al 23 showed no "pop-out" phenomenon with POLARx, while it was observed in 4/97(4.1%) of PVs with Arctic Advance cryoballoon.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pilot studies have shown that POLARx cryoballoon has comparable efficacy, safety, and short-term ablation outcomes compared to Medtronic's cryoballoon. 12,[20][21][22] In a study of 317 patients, Heeger et al 11 did not find any pop-out phenomenon during AF ablation with POLARx. Similarly, Tilz et al 23 showed no "pop-out" phenomenon with POLARx, while it was observed in 4/97(4.1%) of PVs with Arctic Advance cryoballoon.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the intra‐balloon pressure, balloon shape, size and stiffness of POLARx balloon remain stable after freezing starts in contrast to the Medtronic's cryoballoon. Pilot studies have shown that POLARx cryoballoon has comparable efficacy, safety, and short‐term ablation outcomes compared to Medtronic's cryoballoon 12,20–22 . In a study of 317 patients, Heeger et al 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data 3–6 have shown that the acute safety and efficacy of POLARx are similar to those of the AFA‐Pro CB, although the nadir temperatures of POLARx are lower than those of AFA‐Pro. However, limited data on the medium‐term outcome of PV isolation by means of this new CB technology are currently available 7–9 . The aim of this study was to assess the medium‐term outcome of PV isolation by means of the POLARx CB in a large multicenter registry.…”
Section: Introductionmentioning
confidence: 99%
“…The major drawback is a higher risk of nondurable, less transmural lesions, which may contribute to ineffective line of electrical block and longer procedure duration, with a higher risk of veins reconnection. 5 Recent technological advances have paved the way to novel ablation strategies [6][7][8] ; among these, high power (40-50 W) short duration (HPSD) has been proven to be a viable alternative in terms of efficacy and safety. 9 HPSD has been demonstrated to produce larger, more superficial lesions that should not increase complication rate.…”
Section: Introductionmentioning
confidence: 99%